2011
DOI: 10.1002/pros.21375
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatically active prostate‐specific antigen promotes growth of human prostate cancers

Abstract: Background-Prostate specific antigen (PSA) is the best-known member of the kallikreinrelated peptidase family, with an established role as a prostatic disease biomarker. Although it is produced at high levels by all stages of prostate cancer, it is uncertain if PSA plays a role in prostate cancer initiation and progression. We decided to investigate the impact of PSA and its enzymatic activity on tumor cell growth rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 45 publications
(57 reference statements)
2
56
0
Order By: Relevance
“…In vivo, they found that low PSA expression and serum level is associated with lower tumor weight. In addition, they found that low PSA expression is associated with change in expression of many proteins which may indicate that PSA is part of regulatory mechanism of their expressions [40].…”
Section: The Effect Of Low Psamentioning
confidence: 99%
“…In vivo, they found that low PSA expression and serum level is associated with lower tumor weight. In addition, they found that low PSA expression is associated with change in expression of many proteins which may indicate that PSA is part of regulatory mechanism of their expressions [40].…”
Section: The Effect Of Low Psamentioning
confidence: 99%
“…In-gel tryptic digestion was performed on all gel slices (1:20 ratio trypsin enzyme:substrate) for 18 h at 37°C. Mass spectrometric analysis and subsequent protein identifications were performed as described previously (4). …”
Section: Methodsmentioning
confidence: 99%
“…PSA is also produced in high amounts by prostate cancer cells. A role for PSA in the pathobiology of prostate cancer has been proposed based on its effect on prostate cancer growth (4) and its ability to cleave several important growth regulatory proteins (5). However, the exact role for PSA in prostate cancer has yet to be defined clearly.…”
mentioning
confidence: 99%
“…5 Prostate cancer cells disrupt this normal tissue architecture resulting in the leakage of increased amounts of PSA into the tissue interstitium and into the circulation, and it has been shown that enzymatically active PSA confers an enhanced growth rate to human prostate cancer cells, indicating a causal role in prostate cancer progression. 6 The PSA serum test is simple and inexpensive, and it has been a valuable tool in the detection, staging, and monitoring of prostate cancer. However, the PSA assay has always had a disadvantage in that it is not very specific, detecting common pathological conditions such as benign prostatic hyperplasia (BPH) and prostatitis.…”
Section: Introductionmentioning
confidence: 99%